In vitro activity of Triazolo[1,5-a] pyrimidine carboxylic acid extracted from microalgae Hapalosiphon welweschii againstTrichomonas vaginalis - Amal Khalaf (University of Thi-Qar Journal of Science, 2019)
The present study targets the protozoan parasite Trichomonas vaginalis that causes a healthy problems amongwomen and rarely among men , by the application of natural product or secondary metabolites extracted from themicroalgae Hapalosiphon welweschii for the first time in Iraq . methanol extract was explained high activity in threeconcentration recording 100% of parasite death at 200 µg\ml of methanol extract in about two days while 150 and100 µg\ml of extract reports activity against the parasite after three and four days post treatment respectively . GC-Mass spectrum of the methanol extract has explain presence of the compound Triazolo[1,5-a] pyrimidine carboxylicacid in about 13.28 % from the total composition of methanol extract of microalgae H. welweschii .